2011
DOI: 10.1227/neu.0b013e318228490c
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Thrombosis or Stenosis Following Enterprise-Assisted Stent-Coiling: Is It Safe? Midterm Results of the Interstate Collaboration of Enterprise Stent Coiling

Abstract: Midterm occlusion rates are excellent, and stenosis and thrombosis rates are comparable to other available neurovascular stents. Interruption of antiplatelet therapy appears to be a factor in those developing delayed stenosis or thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
86
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(91 citation statements)
references
References 25 publications
4
86
1
Order By: Relevance
“…For example, Mocco et al 5) reported that delayed thrombotic events occurred in 7 of 213 (3%) patients after ESassisted coiling in whom dual AT therapy was terminated. In a similar context, Lee et al 6) reported that delayed infarction occurred in 11 of 261 (4.2%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Mocco et al 5) reported that delayed thrombotic events occurred in 7 of 213 (3%) patients after ESassisted coiling in whom dual AT therapy was terminated. In a similar context, Lee et al 6) reported that delayed infarction occurred in 11 of 261 (4.2%).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] However, some of these patients require suspension of AT if the need for surgery or biopsy arises, and some studies have reported that delayed infarction can occur after cessation or modification of AT in patients who have undergone coiling with ES. [5][6][7] Conversely, long-term AT therapy is associated with a significant risk of hemorrhagic complications. 8,9) Therefore, the aim of our study was to evaluate whether AT could be terminated without increasing the risk of ischemic events among patients who have undergone ES-assisted cerebral aneurysm coiling.…”
Section: Introductionmentioning
confidence: 99%
“…2,6,8) Delayed in-stent occlusion was found in 1 of 110 patients who received stentassisted coil embolization for intracranial aneurysms, and manifested as neurological symptoms. 8) The occlusion occurred after the cessation of double-antiplatelet therapy. 8) Delayed in-stent stenosis occurred in 7 of 156 cases (4.5%).…”
Section: Discussionmentioning
confidence: 99%
“…8) The occlusion occurred after the cessation of double-antiplatelet therapy. 8) Delayed in-stent stenosis occurred in 7 of 156 cases (4.5%). 2) Most were asymptomatic and resolved without additional intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation